PENGARUH GAME ONLINE TERHADAP MOTIVASI BELAJAR REMAJA - Mustika Transmawati; Widya Sartika (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The background of this paper begins with the rise of the issue of technological progress that is growing rapidly in all fields including education. Technology has become one of the needs in every level of society including teenagers today. This has emerged to pro and contra. On the onther side, technological development are very helpful and make many things easier for humans to do their daily activities such as online shopping, business affairs, transportation and others. On the other hand, there are various problems that arise due to the influence of technology in various fields, for example in the field of education. Nowaday, the education is faced with a complex problem. There are students’ low motivation of study and low morale. The purpose of this paper is to discuss about 1) Technological developments in daily life, especially Online Games. 2) Effect of technological development (Online Game) on teenagers / students. 3) How to overcome and prevent Online Game addiction among teenagers / students. Through the directed education, adolescents are prepared to become smart and useful communities for the country and nation. Given the importance of education, there have been many efforts made by educators to improve the quality of education in Indonesia. It is because education is a very important investment for every nation to development a better country.